A cross-sectional analysis identifies a low prevalence of Plasmodium ovale species infections in symptomatic and asymptomatic individuals in Kilifi county, Kenya. [version 4; peer review: 2 approved] - Leonard Ndwiga; Mercy Yvonne Akinyi; Kelvin Muteru Kimenyi; Margaret Chifwete; Victor Osoti; Lynette Isabella Ochola-Oyier (Wellcome Open Research, 2024)
Background The focus on P. falciparum diagnosis has led to an underestimation of the global burden of malaria resulting from neglected Plasmodium species. However, there is still scarce data on the prevalence of P. ovale species (spp) globally. To address this knowledge gap, data collected from cross-sectional studies in Kilifi county were used to: 1) determine the prevalence of P. ovale spp infections; and 2) determine the sensitivity of different diagnostic assays in detecting P. ovale spp infections. Methods A total of 531 individuals were sampled across three study sites in Kilifi County, Kenya between 2009 and 2020. Blood smears were prepared from peripheral blood and screened for Plasmodium parasite stages using light microscopy. Molecular screening involved DNA extraction of dried blood spots and blood in ethylenediaminetetraacetic acid, polymerase chain reaction (PCR) using primers targeting the 18 small ribosomal subunit and sequencing. Results Microscopy screening revealed that the most prevalent species was P. falciparum (32.0%) followed by P. malariae (9.0%) and then P. ovale spp( 1.5%). PCR screening identified additional P. ovale spp positives cases. Overall PCR results indicate that43 (8.1%) out of the 531 individuals harbored P. ovale spp infection with the highest prevalence reported in the tertiary health facility, (14.6%, 95% CI 8-23.6%), followed by the primary health facility (8.3%, 95% CI 5.4-11.9%), and the community from a cross-sectional blood survey, (3.6%, 95% CI 1.2-8.2%). Microscopy screening for P. ovale spp had a low sensitivity of 7% (95% CI 1-19-30%) and a high specificity of 99% (95% CI 98-100%). Sequencing results confirmed the presence of P.ovale curtisi. Conclusions This study provides baseline data for P.ovale spp surveillance in Kilifi County, primarily using PCR to improve diagnosis. These results suggest that malaria elimination and eradication efforts should not only concentrate on P. falciparum but should embrace a holistic approach towards elimination of all Plasmodium spp.